Teaching English Process Through Dialogue Technique at SMP Negeri 1 Poso - Ingriyani Yohana Rawung (Sintuwu Maroso Journal of English Teaching, 2021)
This study aimed to: Describe the process  and students achievement of dialogue technique in teaching English to the seventh grade students at SMP Negeri 1 PosoThe researcher used descriptive qualitative methods to explain the results of the research in teaching learning by dialogue. These results indicate that the students still lack confidence to speak English, students were shy, their voices were no loud during speak English. In pronunciation, intonation and accuracy not correct. Through dialogue, student more confidence, they were no longer shy, their voices more loudly when speak English. The students more encourages and more active when asked to dialogue. They were motivates to improve their ability speaking skill and to make conversation by their pairs. The results obtained from the scores that students dialogue a significant increase. At the first meeting only 54,5% of students fulfill based on standard KKM was 71. At the second meeting was 86,3%. This proves that dialogue was the proper technique to train the students speaking skill especially English